Implementasi Algoritma Rivest Shamir Adleman (RSA) Untuk Keamanan Data Rekam Medik Penyakit Pasien Rumah Sakit - Tobing, Devi Tresia (Jurnal Kajian Ilmiah Teknologi Informasi dan Komputer, 2024)
Medical records are records of the who, what, where, and how of patient care while in hospital. One aspect of the use of medical records is the documentation aspect, namely medical records contain important information that is useful for various parties. Medical records contain data regarding past and present health and contain health professional notes regarding the patient's current condition in the form of physical findings, results of diagnostic and therapeutic procedures and patient responses. Medical record documents belong to doctors, dentists and health service facilities, while the contents of medical records belong to the patient. What can be given, recorded or duplicated by the patient is a summary of the medical record. Patients have the right to know the contents of medical records, however, the entire medical record file can only be held by authorized health/medical records officers and cannot leave the location of the health facility. This aims to maintain medical confidentiality (because medical information can be misused) and prevent medical records from being lost or damaged. To overcome this problem, a computerized system is needed that is able to secure medical record data so that unauthorized parties cannot read it. One technique that can be used to secure medical record data is cryptography. Cryptography comes from Greek which consists of the words kryptos which means hidden and graphia which means something written so that cryptography can be interpreted as something written in secret or hidden.. In applying the Rivest Shamir Adleman (RSA) method in securing medical record data at home Mitra Sejati Medan Hospital, namely by inserting program coding from Shamir Adleman's Rivest method into the programming language used. Next, form a public and private key, then carry out the encryption process for medical record data